Numerical issues related to the calculation of consolidated settlements. - Zarco, Mark H. (Philippine Engineering Journal)
The evaluation of settlements due to consolidation is one of the most common computational procedures in geotechnical engineering. Recent research on this topic has indicated that current computational procedures underestimate consolidation settlements by as much as 70 percent. These errors are believed to result from the over-simplified manner by which the strains are numerically integrated. In this paper, the magnitude and nature of these numerical errors is investigated. A series of numerical experiments are performed to study the effects of load intensity and type, depth of foundation, thickness of soil layer and preconsolidation pressure on these errors. Numerical errors are evaluated by comparing results obtained using the aforementioned procedures to either closed form analytical solutions or numerical solutions using a high precision adaptive quadrature. Results of the numerical experiments indicate that such the underestimation of consolidation settlements is more pronounced in normally consolidated as well as heavily overconsolidated soils as compared to either lightly overconsolidated or underconsolidated soils. Recommendations are made regarding the proper use of the above mentioned procedures in order to guarantee as sufficient degree of accuracy in the calculations.